PERANCANGAN PURWA RUPA MODULASI LEBAR PULSA BERBASIS TIMER 555 DAN IRF 40 - Wahyu Sapto Aji (Universitas Ahmad Dahlan, 2008)
In many applications such of DC motor speed regulation commonly needed DC to DC voltage conversion. The method that frequently use for DC to DC conversion is using chopper circuit. In chopper circuit a DC voltage source being chopped at constant frequency but with variable duty cycle (in this case it’s called as Pulse Width Modulation, PWM). In this research a circuit chopper has been design successfully. The circuit uses 555 timer IC as PWM pulse shaper and IRF 40 power Mosfet as switch device. This circuit prototype successfully tested to drive a 12 watt DC motor at 1200 rpm with voltage at 12 V.